THE INFLUENCE OF SERVICESCAPE ON CUSTOMERS ENGAGEMENT THROUGH CUSTOMER SATISFACTION AT BRASTAGI COTTAGE - Tri Putri Br Purba; Arlina Nurbaity Lubis; Beby Karina Fawzeea Sembiring (CV. Radja Publika, 2025)
This study aims to determine and analyze the influence of customer experience on customer engagement through customer satisfaction at Brastagi Cottage. This study is an associative study and the type of data used is quantitative data. The population in this study is Brastagi Cottage customers whose number is unknown. The number of samples in this study was 140 respondents. The sampling technique used purposive sampling with the criteria of Brastagi Cottage customers who have stayed more than 1 time. The data analysis used is structural equation modeling. The results of this study indicate that customer experience directly have a positive and significant effect on satisfaction and customer engagement at Brastagi Cottage. Indirectly, servicescape and customer experience have a positive and significant effect on customer engagement through customer satisfaction at Brastagi Cottage.